2019
DOI: 10.1101/737049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using indication embeddings to represent patient health for drug safety studies

Abstract: ObjectiveThe electronic health record is a rising resource for quantifying medical practice and discovering adverse effects of drugs. One of the challenges of applying these methods to health care data is the high dimensionality of the health record. Methods to discover effects of drugs in health data must account for tens of thousands of potentially relevant confounders. Our goal in this work is to reduce the dimensionality of the health data with the aim of accelerating the application of retrospective cohor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Foremost, our results display evidence of remaining confounding. We previously showed that the propensity score is not able to model many important types of confounding 15 . This is because the medical record is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Foremost, our results display evidence of remaining confounding. We previously showed that the propensity score is not able to model many important types of confounding 15 . This is because the medical record is incomplete.…”
Section: Discussionmentioning
confidence: 99%